Pengaruh Tax Planning dan Tax Avoidance terhadap Nilai Perusahaan pada Perusahaan Sektor Energi yang Terdaftar di BEI Tahun 2022-2024 - Nurul Aulia Annisa (UNIVERSITAS DHARMAWANGSA, 2026)
The dynamic business environment and fluctuating stock prices of energy sector companies on the Indonesia Stock Exchange have driven the importance of tax management strategies, particularly through tax planning and tax avoidance, to maintain and enhance company value. This study aims to analyze the influence of tax planning and tax avoidance on company value in energy sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The scientific approach employed is a quantitative method using multiple linear regression analysis, utilizing secondary data from 36 energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The results indicate that partially, tax planning (TRR) has a positive and significant effect on company value (0,003), while tax avoidance (CETR) has no significant effect on company value (0,832). Simultaneously, tax planning and tax avoidance have a significant effect on company value.